Gender Classification Based On Mouse Movement Activity On Computer - Muhamad Amirul Amin Ismail (2019)
In this modernized world, technology skills or computer skills are being taught and polished to the new generation as it is a requirement to live a life in this new lifestyle in this coming days. From a simple skill such as the word editing skillto a complex level like a programming coding, people are being taught to allow them to make use of this knowledge for their own livings. In May 2018, the Malaysia National Cyber Security Agency (NCSA) detected a significant growth of cyber threat attempt focusing on a few organisation in Malaysia as reported by the Berita Harian Newspaper. This uprising shows that there are many hackers out there making it too hard to identify. This project is to classify gender based on the data we have obtained through the mouse activity on computer. This project will be carried out by classifying data from computer in WEKA analysing tool.